Pelatihan Pemanfaatan Media Manipulatif Matematika Materi Pengukuran Bagi Guru Sekolah Dasar - Agus Susanta; Irwan Koto; Edi Susanto (JPM: Jurnal Pengabdian Masyarakat, 2023)
Learning mathematics at the elementary school level requires media that can bridge students’ understanding of abstract material. Through the media, students can make mathematics material acceptable. This activity aims to improve the skills of teachers in using manipulative media in mathematics learning material measurement. This activity target is the teachers at State Elementary School Number 78 South Bengkulu with 15 teachers. The activity stages consist of three stages, preparation, training implementation, and evaluation. Teacher skills were observed using pedagogic tests and teacher response questionnaires. The result of this activity is the improvement of teacher skills, the average skill is 67.50 and the teacher's response is in the high category. This activity suggests that the teacher conveys mathematics material in class using media to bridge students in mastering concepts.